1993
DOI: 10.1007/bf00993703
|View full text |Cite
|
Sign up to set email alerts
|

Biological activity of the shrubBoscia senegalensis (PERS.) LAM. ex Poir. (Capparaceae) on stored grain insects

Abstract: Biological activity of leaves, fruits and extract of the African shrubBoscia senegalensis (PERS.) LAM. ex Poir. was evaluated against five stored-grain insects. When added to cowpeas at 2-4% (w/w), fresh ground fruits and leaves caused 80-100% mortality inCallosobruchus maculants (F.) adults and significantly reduced both emergence and damage of the F1 progeny. Acetone fruit extract exhibited a potent fumigant effect onProstephanus truncatus HORN, C.maculatus, andSitotroga cerealella OLIV.; with LT50 values of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0
3

Year Published

1996
1996
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 8 publications
3
12
0
3
Order By: Relevance
“…The findings of the present investigation are in accordance with those of other workers who have previously reported that plant material affected significantly the development of bruchids (Adedire and Akinneye, 2004;Rahman and Talukder, 2006;Shukla et al, 2007;Bamaryi et al, 2007;Seck et al, 1993;Doumma et al, 2006;Toufique et al, 2009).…”
Section: Discussionsupporting
confidence: 93%
“…The findings of the present investigation are in accordance with those of other workers who have previously reported that plant material affected significantly the development of bruchids (Adedire and Akinneye, 2004;Rahman and Talukder, 2006;Shukla et al, 2007;Bamaryi et al, 2007;Seck et al, 1993;Doumma et al, 2006;Toufique et al, 2009).…”
Section: Discussionsupporting
confidence: 93%
“…The insecticidal properties of these two sulphur-containing compounds are well known and their use for pest control in storage systems has been suggested (Seck et al 1993(Seck et al , 1996Auger et al 1994;Thibout and Auger 1997). However, these studies did not analyze the susceptibility of the parasitoids developing in the stores to these sulphur-containing compounds.…”
mentioning
confidence: 99%
“…In Caryedon serratus, the use of products derived from plants repellent or insecticide lags behind other weevils such as Callosobruchus maculatus F. (Seck et al, 1993 ;Seck, 1994 ;Alzouma, 1995 ;Mahgoub, 1995), Callosobruchus analis F. (George and Patel, 1992), Callosobruchus chinensis L. (Pandey and Singh, 1995).…”
Section: Introductionmentioning
confidence: 99%